KAJIAN KERAGAMAN JENIS DAN LAJU PERTUMBUHAN KAPANG DALAM ACAR LIMAU KASTURI (CITROFORTUNELLA MICROCARPA) MARANAN MASY ARAKAT MELAYU - nasution, Muhammad Yusuf; Hasairirr, Ashar; Harsono, Tri (JURNAL PENELITIAN SAINTIKA, 2011)
This research aims to study the diversity of species, growth rate and colony number of mold growth inMusk Lime Pickle in various storage time. The research method is Non Factorial Experiment,complete random sampling (RAL) .. The results indicated that in Musk Lime Pickle, there are 6 moldssuch as: Aspergillus fumigatus, Aspergillus niger, Aspergillus tamari, Fusarium solani, Mucor mucedo,and Penicillium digitatum. The duration of storage decreased the growth rate of mold, and the diversityof mold is not increase. The mold that growth more is Aspergillus fumigatus and Penicillium digitatum, while the least is Mucor mucedo and Fusarium solani. The species of mold found in morenumber in the storage of one week and the few number without treatment.